Real-world persistence with antiretroviral therapy for HIV in the United Kingdom: A multicentre retrospective cohort study. Issue 4 (April 2017) - Lewis, Joseph M.; Smith, Colette; Torkington, Adele; Davies, Craig; Ahmad, Shazaad; Tomkins, Andrew; Shaw, Jonathan; Kingston, Margaret; Muqbill, Ghadeer; Hay, Philip; Mulka, Larissa; Williams, Deborah; et al.
Summary: Objectives: Persistence with an antiretroviral therapy (ART) regimen for HIV can be defined as the length of time a patient remains on therapy before stopping or switching. We aimed to describe ART persistence in treatment naïve patients starting therapy in the United Kingdom, and to describe differential persistence by treatment regimen. Methods: We performed a retrospective cohort study at eight UK centres of ART-naïve adults commencing ART between 2012 and 2015. Aggregate data were extracted from local treatment databases. Time to discontinuation was compared for different third agents and NRTI backbones using incidence rates. Results: 1949 patients contributed data to the analysis. Rate of third agent change was 28 per 100 person-years of follow up [95% CI 26–31] and NRTI backbone change of 15 per 100 person-years of follow up [95% CI 14–17]). Rilpivirine, as co-formulated rilpivirine/tenofovir/emtricitabine had a significantly lower discontinuation rate than all other third agents and, excluding single tablet regimens, co-formulated tenofovir/emtricitabine had a significantly lower discontinuation rate than co-formulated abacavir/lamivudine. The reasons for discontinuation were not well recorded. Conclusions: Treatment discontinuation is not an uncommon event. Rilpivirine had a significantly lower discontinuation rate than other third agents and tenofovir/emtricitabine a lower rate than co-formulated abacavir/lamivudine.